Status Pembiayaan Pertanian pada Sistem Agribisnis Padi Sawah di Kabupaten Konawe dan Konawe Selatan Provinsi Sulawesi Tenggara - Saediman, Haji; Indarsyih, Yusna; Abadi, Musram (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
The study aimed to find out the present status of financing of rice farming in each of its agribusiness sub-system. The study was carried out in Konawe and South Konawe Districts in Southeast Sulawesi Province. Data were collected from rice farmers in the selected farmer groups in 14 subdistricts of the two districts, as well as from processors/Rice Milling Unit, traders, retailers, government staff, and financial institutions (bank and non-banks) using questionnaire-based interviews and Focus Group Discussions. Data were analyzed qualitatively using descriptive statistics. Study results showed that rice farming financing was still dominated by non-formal financial institutions, especially by the traders along the value chain. Farmers did not have sufficient access to formal financial institutions and they preferred to take loans from non-formal money lenders. Loans from banks were chiefly allocated to actors in downstream agribusiness sub-systems, namely processors and traders. Improving the accessibility of smallholder farmers to formal financial institutions should be continuously done to help increase production, income, and prosperity of smallholder farmers.